2022
DOI: 10.34133/2022/9813841
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Preprocessing Combined with Deep Transfer Learning to Evaluate Chlorophyll Content in Cotton Leaves

Abstract: Rapid determination of chlorophyll content is significant for evaluating cotton’s nutritional and physiological status. Hyperspectral technology equipped with multivariate analysis methods has been widely used for chlorophyll content detection. However, the model developed on one batch or variety cannot produce the same effect for another due to variations, such as samples and measurement conditions. Considering that it is costly to establish models for each batch or variety, the feasibility of using spectral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The chlorophyll-to-carotenoid ratio provides insights into leaf functionality because C ab varies dynamically throughout the plant growth cycle, while the carotenoid content remains relatively stable before advanced stage of senescence [37,38]. On the other hand, the reflectance-based model yielded results consistent with previous studies, such as Xiao [19] who established transfer models between different cotton cultivars with R 2 ranging from 0.58 to 0.73. For the models based on reflectance spectra, those employing rice dataset #3 as the training set showed the worst average R 2 and RMSE.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The chlorophyll-to-carotenoid ratio provides insights into leaf functionality because C ab varies dynamically throughout the plant growth cycle, while the carotenoid content remains relatively stable before advanced stage of senescence [37,38]. On the other hand, the reflectance-based model yielded results consistent with previous studies, such as Xiao [19] who established transfer models between different cotton cultivars with R 2 ranging from 0.58 to 0.73. For the models based on reflectance spectra, those employing rice dataset #3 as the training set showed the worst average R 2 and RMSE.…”
Section: Discussionsupporting
confidence: 81%
“…Spectral preprocessing techniques are common methods used to achieve calibration transfer and represent the first step in spectral analysis processing [18]. Xiao [19] found that the transfer model improved after processing with first derivative (FD) and standard normal variate transformation (SNV) compared to traditional partial least squares regression (PLSR) or support vector regression (SVR) models. Additionally, incorporating a portion of new data into the training dataset can improve the transfer learning performance.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the influence of the particle size and surface scattering of the samples ( 21 , 22 ), some noise is included in the acquired original spectra. To improve the prediction accuracy and stability of the detection model, this study used standard normal variation (SNV) to eliminate the noise in the original spectra ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some steps in this pipeline still exhibited low throughput, such as measuring leaf chlorophyll content and leaf photosynthetic light response curves. Multispectral or hyperspectral imaging has been employed to predict leaf chlorophyll content [ 69 ] and photosynthetic parameters [ 70 ]; however, challenges exist due to leaf angle and the distance between the light source and the leaves [ 71 ]. The light response curve can be estimated from leaf chlorophyll fluorescence parameters, including quantum yield of PSII (Φ PSII ) and electronic transport rate under varying light intensities [ 72 ].…”
Section: Discussionmentioning
confidence: 99%